THE ANALYSIS OF POLITENESS MAXIM IN THE ECLIPSE MOVIE - Martin Axcel Panjaitan; Masda Surti Simatupang (DIALEKTIKA: JURNAL BAHASA, SASTRA DAN BUDAYA, 2020)
AbstractMaxim as a politeness principle is a substantial issue because if people obey the regulation, they will enact their expression more thoughtfully. One that corresponded to the principle is the scale of politeness, a measurement of the level of politeness. This paper aimed to analyze politeness maxims and determine the scales of politeness used by the characters’ utterances in the Eclipse movie. The writers used a qualitative descriptive method in this research since the data described the problematic context. The politeness of maxim and scale of politeness were investigated based on Leech’s principle. The phases of analyzes included listing data with politeness maxim and classifying the data into six maxim categories. The next step was analyzing and interpreting the data based on Leech’s scale of politeness used by characters’ utterances. The last was portraying an inference from the result of the analysis. From the analysis of twenty-six data, the most dominant politeness maxim is the generosity maxim (nine data), and the least was the agreement maxim (one data). The rest were seven approbation maxims, six sympathy maxims, and three tact maxims. The politeness scale was cost-benefit (twenty-three data) and optionality (three data).Key Words: politeness maxim, politeness principle, scale of politeness